IMPLEMENTATION OF EXPERIENTIAL LEARNING TO IMPROVE CRITICAL THINKING SKILL OF SMK GRADERS - Mundi Adi, Alif; Lestari, Wahyu (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
This research aims to improve critical thinking skill of X AKL 1 graders of SMK Negeri 2 Magelang with experiential learning implementation. This research is classified as Classroom Action Research (CAR) that conducted with two cycles. Data collection techniques used are test and field notes. Based on the results of the study, it can be concluded that the implementation of experiential learning can improve the critical thinking skill of X AKL 1 graders of SMK Negeri 2 Magelang. In cycle I, the average value of students’ critical thinking skill was 44.8 at the pretest increased by 29 or 64.73% to 73.8 at the posttest. In cycle II, the average value of students’ critical thinking skill was 51 at the pretest increased by 30.9 or 60.59% to 81.9 at the posttest. The students’ learning completeness cycle I was 6% at the pretest increased by 57% to 63% at the posttest. While in cycle II was 18% at pretest increased by 67% to 85% at posttest. The suggestion recommended in this article is that experiential learning methods can be used by teachers to improve students’ critical thinking skills. For other researchers, they can also conduct similar research and examine student responses to the implementation of experiential learning for improvement and refinement in the application of the method.